2014
DOI: 10.1016/j.jagp.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Daily Stressors and Adult Day Service Use by Family Caregivers: Effects on Depressive Symptoms, Positive Mood, and Dehydroepiandrosterone-Sulfate

Abstract: Objectives This study examines effects of daily use of adult day services (ADS) programs by caregivers of individuals with dementia (IWD) on a salivary biomarker of stress reactivity, dehydroepiandrosterone-sulfate (DHEA-S), and whether these effects on DHEA-S are associated with daily variability in positive mood and depressive symptoms. Design We used a daily diary design of 8 consecutive days with alternation of intervention (ADS) and non-intervention days to evaluate within- and between-person effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…This study also found that being able to send a spouse or parent to an adult day service program reduced family caregivers' daily stress levels by about 40% [3]. "Adult day services create a win-win situation for everyone involved," said Elia Femia, a codirector of the research and coauthor of the article.…”
Section: Home and Community Care Block Grant Programsmentioning
confidence: 87%
See 4 more Smart Citations
“…This study also found that being able to send a spouse or parent to an adult day service program reduced family caregivers' daily stress levels by about 40% [3]. "Adult day services create a win-win situation for everyone involved," said Elia Femia, a codirector of the research and coauthor of the article.…”
Section: Home and Community Care Block Grant Programsmentioning
confidence: 87%
“…According to the Penn State study, the improvement in behavior and mood achieved by adult day service program is similar to, or greater than, the improvement provided by available medications for persons with dementia, without the adverse effects [3].…”
Section: Home and Community Care Block Grant Programsmentioning
confidence: 97%
See 3 more Smart Citations